Inovasi Manajemen Pemasaran Pendidikan: Strategi Konten Media Sosial di Pesantren Idrisiyyah Putri Tasikmalaya - Purwanti, Gita Angraeni; Belinda, Ulfi Wisa; Hidayat, Hardi Humaedi (Universitas Hamzanwadi, 2025)
This study aims to explore innovations in educational marketing management through social media content strategies at the Idrisiyyah Islamic Boarding School in Tasikmalaya. The method used was descriptive qualitative with a field research approach. Despite limited human resources, the results of the study indicate significant innovations, such as the formation of a communication and information team and a student creator organization (KSI). Social media accounts, including TikTok and Instagram, were successfully created and showed positive follower growth. Data shows that the implementation of social media content strategies has had a positive impact on increasing the number of new students, from 470 participants in 2020-2021 to 550 participants in 2025- 2026. This study emphasizes the importance of innovation in educational marketing management in the digital era.